On-line personality assessment: Are electronic versions equivalent to the traditional one? - Parmač, Maja (Array, 2007)
The aim of this study was to test the equivalence of five-factor personality questionnaire IPIP100 between three different item presentation modes. The item presentation modes were: traditional paper-and-pencil, electronic identical to paper-and-pencil one and electronic mode with item-by-item presentation. Our research design included dependant samples of psychology students (N=80) and was done in proctored and nonanonymous settings. The results showed that three different questionnaire versions have equivalent factor structures, equal reliabilities, correlations between the same factors at the level expected from their reliabilities, equal means and variances and identical correlation patterns with external variables. Based on the gained data we can conclude that these are basically identical questionnaire forms, i.e. that electronic questionnaire can be used as a substitute for traditional paper-and-pencil version.